Is it possible to scrutinize a relationship between a given pair of actors by performing a documentary scrutiny? - Dias de França, André Luiz; Ataíde Dias, Guilherme (AWARI, 2021)
This is the exploratory stage of data used in a doctoral thesis that used social network analysis to scan relationships between actors with the aim of making the thesis that the exception regime in Brazil for 21 years, was already supported by a cohesive and robust of who shared an ideology. Through documentary research, a social network analysis was used in an innovative way when scrutinizing archives in the search for links between people in the period from 1964 to 1985. 374 people classified in the reports of the National Commission of Truth as responsible for human rights violations during the Dictatorship in Brazil. They are names of owners who made up an initial list of social actors to build the network of human rights violators. Through the construction of a matrix, associated with each author, it performed every fifteen events. To give depth, searches were made in the digital repositories of documents (such as their availability) for the following references: Projeto Brasil Nunca Mais de 1985, from the Archdiocese of São Paulo; National Archives and Brazilian Digital Library. With the findings, it was possible to conclude an exploratory stage with the following: It is possible to scan a relationship between a given pair of actors by conducting documentary scrutiny.